Effects of stretching on muscle strength, endurance, and power performance: A systematic review and meta-analysis - dos Reis, A. L.; de Oliveira, L. C.; de Souza, A. Y. V.; Stabelini Neto, A.; de Oliveira, R. G. (Isokinetics and Exercise Science, 2024)
BACKGROUND: The acute and chronic effects of stretching preceding exercises on strength, power and muscular endurance are still not entirely clear in the literature. OBJECTIVE: To verify the acute and chronic effects of the main types of stretching (static, dynamic, PNF, and ballistic) on muscle strength, power, and endurance. METHODS: A systematic literature search was performed in: PubMed, Web of Science, LILACS, Scopus, Science Direct, and CENTRAL. The methodological quality was assessed using the PEDro scale. Meta-analysis were performed using the standardized mean difference (SMD). RESULTS: 43 studies were included in the systematic review and 30 in the meta-analysis calculations. Only two studies showed high methodological quality. In general, static stretching had an impact on the potentiated the gain in muscle strength of the lower limbs in the long term (0.60 [0.20-1.00]). The acute (ES = 0.38 [0.05-0.70]) and long-term (ES = 1.04 [0.21-1.88]) dynamic stretching was able to potentiate the gain of muscle power in the lower limbs, while the acute PNF had an impact on the worsening of the muscular endurance (ES = 1.68 [0.83-2.53]). CONCLUSIONS: When the training objective is linked to acute effects, dynamic stretching should be prioritized before the main activity. For long-term effects, static and dynamic stretching have been shown to potentiate muscle strength and power gain, respectively, and are recommended in these cases.